Sleep loss and change detection in simulated driving. (2nd October 2020) - Filtness, A. J.; Beanland, V; Miller, K.A.; Larue, G. S.; Hawkins, A
ABSTRACT: Driver sleepiness is a leading contributor to road crashes. Sleep-related crashes are more likely to involve collision with a stationary object than non-sleep-related crashes. The mechanism underpinning this is unknown; one potential explanation may be an increased propensity for change blindness. Twenty-four drivers with at least one year of independent driving experience completed two simulated drives: one following a normal night of sleep (7–8 h) and one following sleep restriction (5 h). The drive consisted of 5 laps of an 11.3 km circuit, taking approximately 45 min. Each lap comprised half urban and half rural driving environments. Twenty times during the drive the visual screen was blanked for 500 ms, and when it reappeared participants were asked whether there were any changes. Twelve times a change occurred, and eight times no change occurred. Additionally, four unexpected changes occurred; for example, the language of the road signs was changed from English to German. At the end of each drive, participants were asked if anything unusual occurred. Sleep loss resulted in significantly increased subjective sleepiness and subjective workload. Driving in an urban environment did not increase alertness; subjective sleepiness ratings did not significantly differ between urban and rural environments. Change detection accuracy for both cued and unexpected changes was not significantly affected by sleep loss. In line with previous research, accuracy was greater for changes with high safety relevance and those occurring in rural environments. Collectively the findings of the study suggest that increase change blindness is probably not a contributor to sleep-related road crashes; however, future on-road research and with greater levels of sleep loss is needed to confirm findings.